(untitled) (Scientific journal of the Fergana State University, 2023)
The article traces the main periods of cooperation in the fields of politics, economics and security. The author shows that since gaining independence to this day, a lot of work has been done in these areas. This is the establishment of bilateral relations, the establishment of diplomatic relations, the opening of embassies and consulates, the implementation of visits at the highest level, at the level of chairmen of missions, ministers of defense and law and order.